Incidence and resolution of de novo hydronephrosis after pediatric robot-assisted laparoscopic extravesical ureteral reimplantation for primary vesicoureteral reflux. Issue 4 (August 2022) - Mittal, Sameer; Eftekharzadeh, Sahar; Aghababian, Aznive; Weaver, John; Fischer, Katherine; Long, Christopher J.; Weiss, Dana A.; Van Batavia, Jason; Srinivasan, Arun K.; Shukla, Aseem R.
Summary: Introduction: With the advent of robot-assisted laparoscopic ureteral reimplantation (RALUR) for primary vesicoureteral reflux (VUR), understanding and minimizing its complications continues to be critical. Incidence of de novo hydronephrosis after RALUR could be indicative of an outcome that needs further study or could be a benign transient finding. Objective: In the present study, we hypothesized that the incidence of de novo hydronephrosis after RALUR is low and resolves spontaneously. Methods: An IRB-approved prospective single-institutional registry was utilized to identify all patients undergoing RALUR via an extravesical approach from 2012 to 2020. Patients with primary VUR and minimal (Grade I SFU) or no hydronephrosis prior to surgery were included. Patients who had other associated pathology or underwent concomitant procedures were excluded. Preoperative characteristics including VUR and hydronephrosis grades as well as post-operative clinical details and hydronephrosis grades were aggregated and analyzed. Results: 86/172 (50%) patients (133 ureters), with median reflux grade of 3 (IQR: G2, G3) met the inclusion criteria. Patients underwent RALUR at a median age of 5.7 years (IQR: 3.4, 8.7) with median 36.2 months (IQR: 19.6, 63.6) follow-up. Renal ultrasound at 4–6 weeks post-op showed de novo hydronephrosis in 18 (13.5%) ureters; the complete resolution was seen in 13 ureters (72%) at a median of 4.5 months from surgery. Among the 5 with non-resolved hydronephrosis (SFU G2:4, G3:1), 2 patients (3 ureters) underwent subsequent interventions. Discussion: The present study evaluating the natural history of de novo hydronephrosis after RALUR-EV performed for primary VUR, is to our knowledge the largest cohort of patients undergoing RALUR that this has been studied in. In our cohort, the incidence of de novo hydronephrosis after RALUR was 13.5%, similar to rates reported in two OUR cohorts, and significantly lower than reported incidence rates of 22–26% in several OUR cohorts, and 30% in a RALUR cohort. In the present cohort, hydronephrosis resolved spontaneously in more than 72% of cases. The median time from surgery until resolution of hydronephrosis was 4.5 (1.6, 10.5) months, which is shorter in comparison to the average time to resolution of 7.6 months, reported by Kim et al. in an earlier study. Conclusions: De novo hydronephrosis after RALUR can be followed with serial renal ultrasounds. The majority of de novo hydronephrosis post-RALUR is transient and resolves spontaneously within a year of surgery with a very low re-intervention rate. Summary Table Summary Table Number of Patients 86 Number of ureters 133 Age at surgery (years), median (IQR) 5.7 (3.4, 8.7) Follow-up duration (months), median (IQR) 36.2 (19.6, 63.6) Worsened/de novo hydronephrosis after RALUR 18 (13.5%)  Grade 2 14 (10.5%)  Grade 3 2 (1.5%)  Grade 4 2 (1.5%) Resolution of de novo hydronephrosis 13 (72.2%) Time to hydronephrosis resolution (months), median (IQR) 4.5 (1.6, 10.5) Procedures performed after RALUR 3 (16.7%)